Democracy for whom? How criminal punishment marginalizes the political voices of Black and Brown Americans. Issue 2 (8th December 2022) - Remster, Brianna; Kramer, Rory
Abstract: U.S. racialized punishment practices have long harmed communities of color in sundry ways, including access to democratic processes. Synthesizing scholarship on punishment and democracy that centers the lived experiences and political subjectivities of Black and Brown Americans, we argue that criminal punishment is a powerful form of political marginalization that diminishes the political voices of Black and Brown Americans en masse and simultaneously amplifies the voices of White Americans. To illuminate how punishment (re)produces systemic racial inequities in democratic processes, we focus on two distinct but related marginalizations: disenfranchisement for a felony conviction and prison gerrymandering. These deep‐rooted "colorblind" policies did not draw scholarly attention until recent decades, well after district boundaries and election outcomes across the country were impacted. To help understand that delay, we highlight the utility of applying an emancipatory, Du Boisian lens with an example from our past work. Looking to the future, we argue that DuBois's tenets should inform punishment scholarship regardless of methodology or data type. Doing so will help identify more hidden forms of political marginalization in a timely manner, enable scholars to investigate the potential multiplicative effects of those marginalizations, and increase the potential impact of that work beyond the academy.